1987
DOI: 10.1172/jci112831
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotonic agent milrinone stimulates resorption in rodent bone organ culture.

Abstract: MethodsThe cardiotonic agent amrinone inhibits bone resorption in vitro. Milrinone, an amrinone analog, is a more potent cardiotonic agent with lower toxicity. In contrast to amrinone, milrinone stimulated resorption in cultures of neonatal mouse calvaria and fetal rat limb bones. Threshold doses were 0.1 l&M in calvaria and 0.1 mM in limb bones; maximal stimulation occurred in calvaria at 0.1 mM. Maximal responses to milrinone and parathyroid hormone were comparable. Milrinone concentrations below 0.1 mM did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
1

Year Published

1988
1988
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 19 publications
2
3
1
Order By: Relevance
“…In these studies, increased calcium and lysosomal enzyme release, as well as decreased bone calcium, Pi, and hydroxyproline content were found following thyroid hormone treatment. Furthermore, the slow de- velopment of bone resorption observed with T, in the current investigation was aligned closely with the delayed time courses of thyroid hormone-stimulated calcium release, which have been reported previously in fetal rat limb bones (7) and in neonatal mouse calvariae (9,11). Thyroid hormone action is thought to be initiated by the binding of iodothyronines to specific target cell nuclear receptors, and high affinity nuclear receptors for the thyroid hormones have been reported in osteosarcoma cells (36,37) and in neonatal mouse calvariae (10).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In these studies, increased calcium and lysosomal enzyme release, as well as decreased bone calcium, Pi, and hydroxyproline content were found following thyroid hormone treatment. Furthermore, the slow de- velopment of bone resorption observed with T, in the current investigation was aligned closely with the delayed time courses of thyroid hormone-stimulated calcium release, which have been reported previously in fetal rat limb bones (7) and in neonatal mouse calvariae (9,11). Thyroid hormone action is thought to be initiated by the binding of iodothyronines to specific target cell nuclear receptors, and high affinity nuclear receptors for the thyroid hormones have been reported in osteosarcoma cells (36,37) and in neonatal mouse calvariae (10).…”
Section: Discussionsupporting
confidence: 91%
“…Prostaglandin's (especially those of the PGE series) are known to be potent stimulators of bone resorption (42), and the compounds are suggested to be important local mediators of bone resorption (13). However, unlike previous studies in neonatal mouse calvariae, which have shown inhibition of calcium release by indomethacin (8, 9,11) and increased PGE, and PGI, formation following thyroid hormone treatment (1 l), calcium release elicited by T4 and T, in the present investigation was not inhibited by indomethacin, and T, treatment did not increase PGE, and PGI, formation. In a recent study by Klaushofer et al (1 1) using neonatal mouse calvariae, it was reported that the percentage of calcium released following thyroid hormone administration showed greater variation than did release stimulated by other resorptive agents.…”
Section: T4 and T Stimulation Of Bone Resorptioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Medium ␤-glucuronidase activity was determined colorimetrically using phenolphthalein glucuronidate (Sigma, St. Louis, MO) as a substrate (31).…”
Section: ␤-Glucuronidase Activitymentioning
confidence: 99%